TRPM4 contributes to cell death in prostate cancer tumor spheroids, and to extravasation and metastasis in a zebrafish xenograft model system - Florian Bochen; Saurav Subedi; Federico La Manna; Sofia Jarrin; Irida Papapostolou; Marianna Kruithof‐de Julio; Christine Peinelt (Molecular Oncology)
Transient receptor potential melastatin‐4 (TRPM4) ion channel expression is upregulated in prostate cancer (PCa), contributing to increased cell proliferation, migration, adhesion, epithelial‐to‐mesenchymal transition, cell cycle shift, and alterations of intracellular Ca2+ signaling. GEO2R platform analysis of messenger RNA (mRNA) expression of ~ 6350 genes in normal and malignant prostate tissue samples from 15 PCa patients demonstrates that TRPM4 expression is upregulated sixfold and is among the most significantly upregulated genes in PCa. We find that absence of TRPM4 reduced PCa tumor spheroid size and decreased PCa tumor spheroid outgrowth. In addition, lack of TRPM4 increased cell death in PCa tumor spheroids, a phenotype that is absent in two‐dimensional (2D) cancer cell systems. Lastly, absence of TRPM4 in PCa cells reduced extravasation and metastatic burden in a preclinical zebrafish cancer model. Taken together, our findings show that TRPM4 is an attractive therapeutic target in PCa and highlights the need for future development of pharmacological tools.